Comparative evaluation of speed of orthodontic tooth movement with or without piezocision technique: An In vivo study - Nirali Rathod; Sonali Vijay Deshmukh; Sanket Agarkar; Lakshmi Shetty; Sandeep Jethe; Jayesh S Rahalkar (Wolters Kluwer Medknow Publications, 2019)
Background: Last decade has seen a surge of many innovative techniques aimed at decreasing the length of orthodontic treatment. In this study, the efficiency of canine retraction between piezocision and conventional retraction group has been evaluated and compared. Materials and Methods: A total of ten patients (above 18 years) with Class II division I malocclusion or bimaxillary protrusion which requires individual canine retraction after maxillary first premolar extractions were included in the study. Each patient's maxillary arch was divided into the right and left quadrants. Experimental and conventional sides were randomly allocated. The incisions were given through the periosteum using a piezosurgical knife on the experimental side. Bilaterally, in both the groups, canine retraction was initiated using elastic chain applying 120 g of force on both sides. Follow-up was done every 2 weeks for activation. Results: As compared to the conventional approach, piezocision is 1.5 times faster. Conclusion: Piezocision is an efficient technique that aids an orthodontist to accomplish speedy orthodontic tooth movement without other detriments of the substantially time-consuming and traumatic surgical approaches. Other advantages include decreased surgical procedural time and nominal postoperative discomfort to the patients.